2022
DOI: 10.1021/acsaem.1c03967
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preparation of a CeVO4/Zn0.5Cd0.5S S-Scheme Heterojunction for Efficient Photocatalytic Hydrogen Evolution

Abstract: Improving the separation efficiency of photoinduced electron−hole pairs plays a vital role in preparing highperformance photocatalysts. Here, based on the good light corrosion resistance and excellent visible light response of Zn 0.5 Cd 0.5 S, as well as the unique catalytic, optical, and electrical properties of CeVO 4 , we tightly loaded CeVO 4 on Zn 0.5 Cd 0.5 S by physical coupling to overcome its severe photogenic carrier recombination and obtained a highly efficient photocatalytic catalyst for hydrogen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…As shown in Figure d,e, the slope of the E -– C 2 curve before the introduction of copper is positive, reflecting its n-type semiconductor properties. In Figure f, it is clear that the composite catalyst has two linear regions in the plot, and it is found that the Fermi energy levels are displaced due to the formation of a double S-scheme heterojunction . As we all know, the position of the Fermi level of a semiconductor can be roughly estimated based on the flat band potential.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure d,e, the slope of the E -– C 2 curve before the introduction of copper is positive, reflecting its n-type semiconductor properties. In Figure f, it is clear that the composite catalyst has two linear regions in the plot, and it is found that the Fermi energy levels are displaced due to the formation of a double S-scheme heterojunction . As we all know, the position of the Fermi level of a semiconductor can be roughly estimated based on the flat band potential.…”
Section: Resultsmentioning
confidence: 93%
“…In Figure 9f, it is clear that the composite catalyst has two linear regions in the plot, and it is found that the Fermi energy levels are displaced due to the formation of a double S-scheme heterojunction. 32 As we all know, the position of the Fermi level of a semiconductor can be roughly estimated based on the flat band potential. By actual measurement, the flat band potential and band gap of CoP are −0.36 and 1.91 eV, respectively.…”
Section: α υ υmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1972, when Fujishima and Honda pioneered hydrogen generation using rutile titanium dioxide (TiO 2 ) electrodes, a variety of methodologies have been utilized to research and build effective water separation systems. [7][8][9] Among these, the fabrication of S-scheme heterojunctions is a potential method for the creation of highly effective photocatalysts. 10 Economically, semiconductor materials with favorable photocatalytic characteristics should be synthesized using common elements, making it critical to develop alternatives for precious metals.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen production from solar is widely considered to be among the most viable methods for generating renewable energy. Since 1972, when Fujishima and Honda pioneered hydrogen generation using rutile titanium dioxide (TiO 2 ) electrodes, a variety of methodologies have been utilized to research and build effective water separation systems 7‐9 . Among these, the fabrication of S‐scheme heterojunctions is a potential method for the creation of highly effective photocatalysts 10 .…”
Section: Introductionmentioning
confidence: 99%